Korea’s Balloon War: Symbolic Activism and Propaganda Amid Nuclear Tensions - Kusumawikan, James William; Subhan, Muhammad (Jurnal Hubungan Internasional, 2025)
Balloon propaganda in the Korean Peninsula has long served as a symbolic confrontation between North and South Korea, but the recent “trash balloon war” in 2024 marks a significant shift in both intensity and strategic messaging. This research explores how balloon activism—particularly by North Korean defector- activists—functions as psychological warfare and symbolic resistance in the broader context of inter-Korean rivalry. Through the lens of the Propaganda Model and Symbolic Politics Theory, the study examines how non-state actors utilize symbolic tools to influence public narratives, challenge ideological boundaries, and provoke state-level responses. It also highlights how balloon campaigns, though often framed as humanitarian efforts, can escalate diplomatic tensions and feed into militarized stalemates. By analyzing key events, discourse, and reactions from both Koreas, this study offers a deeper understanding of how seemingly low-tech propaganda tools can carry high-stakes implications. The findings contribute to broader discussions on civil activism, media politics, and geopolitical signaling in the region. Keywords: Balloon Propaganda; Inter-Korean Conflict; Symbolic Politics; Civil Activism.